PENERAPAN MEDIA INTERACTY BERBASIS DEEP LEARNING UNTUK MENINGTAKAN PEMAHAMAN KONSEP SISWA PADA MATERI EKOSISTEM - Azmi, Nabila Firizqi; R, Muhammad Raihan Zaki Guntur Putra; Azhar, Naufal; Rahman, Niken Aulia; Jasmine, Queen Lathifa; Murtadho, Rafi Azzam; Maryanti, Sri (Natural Science Education Research, 2026)
This study aims to identify the implementation of the Interacty digital learning media based on deep learning in improving students’ conceptual understanding of ecosystem material at the junior high school level. Technology-based media are highly needed to help students grasp abstract concepts related to ecosystems. However, the media commonly used so far, such as PowerPoint and YouTube, are considered insufficient to fully support deep learning because they lack interactivity and do not encourage in- depth conceptual analysis. This condition is further exacerbated by students’ low learning motivation, limited school facilities such as the absence of laboratories and minimal practicum tools and learning activities that remain dominated by conventional lecture-based methods. This study employed a weak experimental design, characterized by the use of a pretest administered before treatment and a posttest after treatment. Data were collected through tests and observations. The pretest and posttest results were analyzed using a manual paired t-test to determine the significance level of students' learning outcomes after using Interacty media based on deep learning. The statistical analysis produced a paired t-test score of t = 14.88 with p below 0.001, indicating that the Interacty media is highly effective in improving students’ conceptual understanding.